Adaptation of practice guidelines to prevent functional decline in hospitalized elderly in Iran - Akram Karimi; Mahrokh Keshvari; Maryam Moghimian (Wolters Kluwer Medknow Publications, 2022)
Background: In Iran, many efforts have been made to improve the Quality of Life (QOL) of the elderly; however, despite the efforts made, there is no practice guideline based on the consensus of experts that can be used to prevent the functional decline of hospitalized elderly. Accordingly, the present study was conducted with the aim of adaptation of a practice guideline to prevent the functional decline of hospitalized elderly. Materials and Methods: This study is a developmental study based on the adaptation steps of the practice guideline. First, a search was conducted in 8 databases. The only practice guideline that met the inclusion criteria was then evaluated by the research team using the Appraisal of Guidelines for REsearch and Evaluation (AGREE II) tool. After content analysis of this guideline, the recommendations were categorized in the Canadian Senior Friendly Care (sfCare) Framework and according to the community conditions. Relevant evidence was used to supplement the content. The draft practice guideline was evaluated and modified in two expert panels through the RAND technique. Results: The categorized recommendations were developed in the eight chapters of introduction to the prevention of functional decline of the elderly, general practice guideline, organizational support, care processes, physical ecology, emotional and behavioral environment, ethics in care, and evaluation of function. Conclusions: To prevent functional decline in hospitalized elderly individuals according to the adaptive practice guideline, the hospital and health team need to be aware of support, care processes, and effective function appraisal to be able to provide care with coherent and coordinated solutions.